2020
DOI: 10.1021/acs.jpcb.0c03230
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Approximate 3D-Reference Interaction Site Model (RISM) Molecular Solvation Theory to Acetonitrile as Solvent

Abstract: The integral equation formalism based reference interaction site model (RISM) molecular solvation theory is applied to pure liquid acetonitrile and water–acetonitrile binary mixtures of different compositions. Solvate formation of d- and f-block ions by ACN is also calculated to check applicability of the RISM theory. The generalized Amber force field (GAFF) and the universal force field (UFF) parameters were found to be suitable for applications with the RISM theory for acetonitrile solvent. The presence of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 68 publications
0
6
0
Order By: Relevance
“…Non-polar solvents that are modeled using the 3D-RISM-KH theory are hydrocarbons (hexadecane, cyclohexane), haloalkane (chloroform), and alcohol (n-octanol, t-butanol) [ 41 , 47 , 101 , 102 ]. Other solvents like nitro-compounds (nitromethane, nitroethane, and nitrobenzene), acetonitrile, and dimethyl sulfoxide (DMSO) were also used in RISM-KH calculations for both liquid structure and solvation energetic studies [ 42 , 103 , 104 ]. The performance of the 3D-RISM-KH calculations is summarized in Table 1 .…”
Section: Molecular Solvation Energy Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-polar solvents that are modeled using the 3D-RISM-KH theory are hydrocarbons (hexadecane, cyclohexane), haloalkane (chloroform), and alcohol (n-octanol, t-butanol) [ 41 , 47 , 101 , 102 ]. Other solvents like nitro-compounds (nitromethane, nitroethane, and nitrobenzene), acetonitrile, and dimethyl sulfoxide (DMSO) were also used in RISM-KH calculations for both liquid structure and solvation energetic studies [ 42 , 103 , 104 ]. The performance of the 3D-RISM-KH calculations is summarized in Table 1 .…”
Section: Molecular Solvation Energy Calculationsmentioning
confidence: 99%
“…This makes the RISM formalism an excellent candidate from the perspective of building materials of desired properties, as the theory provides understanding of all the underlying interactions between different constituent fragments. The RISM theory with the integral equation formalism was developed and used for solvation structure and energetics calculations, although the potential of this theory goes beyond regular solvation energy calculations and expands to molecular partitioning, physical-chemical property calculation, and molecular simulations [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. The key feature of the RISM theory is that it can provide reasonably accurate result rapidly, a feature that made this the theory an essential part of the multiscale modeling framework ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…The acetonitrile molecules and the counterions were described with GAFF [48] in the same way as in the classical MM MD simulations, see below. It was previously shown that GAFF describes this particular solvent very well [55,56]. In order to account for the electrostatic interactions between the QM nuclei and the MM point charges that enter the Hamiltonian, a cutoff of 10 Å was applied.…”
Section: Qm/mm MD Reference Simulationsmentioning
confidence: 99%
“…Refs. [ 7 , 8 , 9 , 10 , 11 ] These corrections have been shown to produce HFEs of similar quality to explicit solvent calculations, and have been extended to correct entropy [ 12 ] as well as other solvents [ 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. While other approaches exist, such as creating new bridge functionals [ 11 ] or using hard-sphere liquids as a reference [ 20 ], most have employed corrections based on the partial molar volume (PMV).…”
Section: Introductionmentioning
confidence: 99%